Medicínské, právní a etické aspekty zachování fertility u onkologických pacientek - Záhumenský, J; Kucera, E; Kosová, T; Zmrhal, J; Stejskal, M; Stejskal, D (Ceska gynekologie, 2012)
In recent years the number of the young women in fertile age which are oncologically treated is increasing. For these women chemotherapy and radiotherapy introduces potential risk of reproductive dysfunctions. Present techniques of assisted reproduction are offering possibilities to save reproductive functions even after the oncological treatment. As a perspective outlook seems to be frozen premature oocytes with IVM and fertilisation. With these fertility savings methods are naturally coming up some of the ethical and legal issues.
Keywords: přežívající; těhotenství; Primary Ovarian Insufficiency; kryoprezervace; Cryopreservation; zachování plodnosti; Antineoplastic Agents; primární ovariální insuficience; Neoplasms; Oocytes; ženské pohlaví; protinádorové látky; oocyty; Humans; Pregnancy; nádory; ovarium; Ovary; Blastocyst; Female; blastocysta; lidé; Survivors; Fertility Preservation